CO2 permeability and carbonic anhydrase activity of rat cardiomyocytes. (15th May 2017) - Arias‐Hidalgo, M.; Al‐Samir, S.; Weber, N.; Geers‐Knörr, C.; Gros, G.; Endeward, V.
Abstract: Aim: To determine the CO2 permeability (PCO 2 ) of plasma membranes of cardiomyocytes. These cells were chosen because heart possesses the highest rate of O2 consumption/CO2 production in the body. Methods: Cardiomyocytes were isolated from rat hearts using the Langendorff technique. Cardiomyocyte suspensions exhibited a vitality of 2–14% and were studied by the previously described mass spectrometric 18 O‐exchange technique deriving PCO 2 . We showed by mass spectrometry and by carbonic anhydrase (CA) staining that non‐vital cardiomyocytes are free of CA and thus do not contribute to the mass spectrometric signal, which is determined exclusively by the fully functional vital cardiomyocytes. Results: Lysed cardiomyocytes yielded an intracellular CA activity for vital cells of 5070; that is, the rate of CO2 hydration inside the cell is accelerated 5071‐fold. Using this number, analyses of the mass spectrometric recordings from cardiomyocyte suspensions yield a PCO 2 of 0.10 cm s −1 (SD ± 0.06, n = 15) at 37 °C. Conclusion: In comparison with the PCO 2 of other cells, this value is quite high and about identical to that of the human red cell membrane. As no major protein CO2 channels such as aquaporins 1 and 4 are present in rat cardiac sarcolemma, the high PCO 2 of this membrane is likely due to its low cholesterol content of about 0.2 (mol cholesterol)·(mol total membrane lipids) −1 . Previous work predicted a PCO 2 of ≥0.1 cm s −1 from this level of cholesterol. We conclude that the low cholesterol establishes a PCO 2 high enough to render the membrane resistance to CO2 diffusion almost negligible, even under conditions of maximal O2 consumption of the heart.